Influência da declividade na distribuição da concentração de substâncias poluentes em rios urbanos - Andrade, Carla Freitas de (2004)
With the objective of analyzing the behavior of the concentration of a pollutant substance in urban rivers, subject to the propagation of a kinematic wave, a mathematical model was formulated, based on the Equations of Hydrodynamics, combined with the Equation of Transport Process. For the solution of the differential equations present in the model, the Finite Difference Method was applied. A computer program QUARI (Analysis of Water Quality in Urban Rivers), written in FORTRAN 90, developed for this research, was used for the accomplishment of the simulations. To evaluate the capability and efficiency of the computer program QUARI, several examples were analyzed and the results compared with other results presented in the literature, showing an excellent agreement. By using the computer code QUARI, several simulations varying the channel bottom slope were performed with the purpose to evaluate the influence of this hydraulic parameter on the concentration distribution. The results show that the behavior of the concentration distribution depends strongly on this hydraulic parameter that is decisive in the flow regime of these bodies of water.